2022
DOI: 10.3390/app12084031
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Radio-Frequency Quadrupole Accelerator for the HL-2A/2M Tokamak Diagnostic System

Abstract: In order to figure out the migration and deposition of impurities on the first wall of HL-2A/2M tokamak, Peking University and Southwestern Institute of Physics are co-developing a deuteron RFQ as part of the in situ ion-beam diagnostic for the material. The RFQ, which operates at 162.5 MHz, is designed to accelerate a 10-mA deuteron beam from 40 keV up to 1.5 MeV. Key design considerations and the final design parameters are presented. The RFQ has been conditioned at a 1% duty factor for 80 h at RF cavity pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…To ensure stable operation, the vacuum level was set at 10 −6 is limited gas conductance between quadrants, attaining vacuum uniformity is challenging. Previous RFQ experiments with similar vacuum system [35] demonstrated that two adjacent quadrants can maintain similar pressures by using only one vacuum window, as shown in Figure 32 for our vacuum system.…”
Section: Vacuum Designmentioning
confidence: 54%
“…To ensure stable operation, the vacuum level was set at 10 −6 is limited gas conductance between quadrants, attaining vacuum uniformity is challenging. Previous RFQ experiments with similar vacuum system [35] demonstrated that two adjacent quadrants can maintain similar pressures by using only one vacuum window, as shown in Figure 32 for our vacuum system.…”
Section: Vacuum Designmentioning
confidence: 54%
“…RFQ accelerators can simultaneously focus, bunch, and accelerate low-energy and high-intensity beams; high-intensity RFQ accelerators have a number of applications such as a common front-end injector for high-energy accelerators [1,2], accelerator-based diagnostics in magnetic fusion devices [3,4], and a compact neutron source for radiography and cancer therapy [5,6].…”
Section: Introduction 1rfq Conceptmentioning
confidence: 99%